Prototype Robotic Pool With Fuzzy-Based Decision System - Chua , Shing Chyi (2005)
In this thesis, a wireless robotic pool player is built. The robotic system serves as a prototype for vision and image processing, ball/path trajectory and robot mechanics. Miniature pool table and mini pool balls set are used for evaluating the prototype.